Revolutionizing Material Flow and Handling: Industry 4.0 Integration in Logistics Management - Mukesh Ganchi (International Journal of Advanced Robotics and Automation Technology, 2024)
The integration of Industry 4.0 technologies has become pivotal in reshaping material flow and handling paradigms within logistics management. This paper presents an in-depth analysis of this transformative phenomenon. Industry 4.0's emergence has heralded an era of unprecedented automation, seamless data exchange, and cutting-edge technologies, fundamentally altering conventional logistics practices. Through an extensive review of recent literature, this study meticulously examines the profound impact of Industry 4.0 on material flow and handling dynamics, delineates the pivotal technologies driving this transformation, and meticulously evaluates the ensuing benefits and challenges. Moreover, this paper delves into the ramifications of Industry 4.0 integration on logistics management strategies, elucidating potential pathways for optimizing material flow and handling processes in the contemporary landscape.
Keywords: Automation; Industry 4.0; advanced logistics; logistics management; material flow; strategic management; technology integration